Lethal Effects of Treatment with a Special Dimeticone Formula on Head Lice and House Crickets (Orthoptera, Ensifera: Acheta domestica and Anoplura, Phthiraptera: Pediculus humanus) - Richling, Ira; Böckeier, Wolfgang (Arzneimittelforschung, 2008)
The present study provides the first convincing explanation of the mode of action of the medical device NYDA®, a special dimeticone (CAS 9006-65-9) formula containing 92 % of two dimeticones with different viscosities specifically designed for the physical treatment of head lice infestations (pediculosis capitis) by suffocation. Both, lice (Pediculus humanus) and house crickets (Acheta domestica) treated with this anti-head lice product are knocked out to the status “of no major vital signs” within less than 1 min that in consequence is accompanied irreversibly with the death of the respective insects. Scanning electron microscopical investigations have revealed that the cuticle is coated by a thin closed layer of the dimeticone formula that also enters the stigmata. In vivo observations and dissections of Acheta domestica have shown that application of the medical device to the thoracic stigmata invariably leads to rapid death; this is strongly correlated with the influx of the special dimeticone formula into the head trachea, whereby the solution effectively blocks the oxygen supply of the central nervous system.Dissections after application of the stained product show that it also enters the finest tracheal branches. Analogous in vivo observations in Pediculus humanus have confirmed the correlation between the disappearance of major vital signs and the displacement of air by the dimeticone formula in the tracheal system of the head. For both insect species, statistical data are provided for the chronological sequence of the filling of the tracheal system in relation to the respective vitality conditions of the insects. On average, the special dimeticone formula reaches the insect’s head tracheae within 0.5 min in house crickets and in less than 1 min in lice with a complete filling of the entire head tracheal system of lice within 3.5 min. In addition, a timed sequence of images illustrates this process for lice. The experiments clearly reveal the exclusive and pure physical mode of action of the tested dimeticone formula.
Keywords: CAS 9006-65-9; Dimeticone, effect on head lice, medical device; NYDA®, effect on head lice, medical device; Pediculicides; Pediculus humanus, physical treatment, trachea